The Use of Games in Mathematics Learning: An Experience with Primary School Teachers - Andreia Hall; Nuno Bastos; Sónia Pais; Paola Morando; Maria Luisa Sonia Spreafico (Indagatio Didactica)
This article presents a workshop aimed at teachers from the 1st to 6th grades on the use of games as a pedagogical strategy for teaching mathematics. The workshop, part of the Mathematics in the Early Years 2024 conference, included the exploration of five educational games – Euclid’s Regatta, Garden Animals, Monster Samples, Islands Game, and Mathematical Twins – each one designed to address different mathematical topics, such as Euclidean geometry, descriptive statistics, rational numbers, and mathematical communication. The playful approach adopted aimed to promote the understanding of mathematical concepts through experimentation and interaction, emphasizing the importance of concrete manipulation and mathematical communication in the learning process. One of the highlights was the use of origami to explore geometric axioms, allowing for mathematical constructions as alternatives to those performed with a ruler and compass. To assess participants’ perceptions of the use of gamification in the teaching-learning process of mathematics, a questionnaire was conducted. The results indicate that teachers recognize the potential of games in motivating students, as well as in engaging them in the teaching-learning process, contributing to better academic performance. Additionally, they suggest that participants intend to incorporate this resource into their teaching practices. The experience reinforces the need to integrate interactive approaches in education, highlighting the applicability of educational games as effective tools for improving student engagement and performance in mathematics.